Cyclocarya paliurus Triterpenoids Improve Diabetes-Induced Hepatic Inflammation via the Rho-Kinase-Dependent Pathway - Jiang, Cuihua; Wang, Yiting; Jin, Qiaomei; Zhang, Dongjian; Gao, Meng; Yao, Nan; Yin, Zhiqi; Zhang, Jian; Ma, Shiping (Frontiers in Pharmacology, 2019)
This study aimed to assess the effects of triterpene extract of Cyclocarya paliurus (Batal.) Iljinskaja (CPT) on diabetes-induced hepatic inflammation, and to unveil the underlying mechanisms. Diabetes in db/db mice was alleviated after CPT administration, as assessed by the oral glucose tolerance test. In addition, treatment with CPT dramatically reduced serum insulin, aspartate amino-transaminase, alanine aminotransferase, triglyceride and total cholesterol amounts. Besides, serum levels of interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α were also reduced after CPT administration. Western blot analysis revealed that CPT treatment significantly reversed the protein expression levels of Rho, ROCK1, ROCK2, p-P65, p-IκBα, p-IKKα, p-IKKβ in liver samples obtained from db/db mice. Upon palmitic acid stimulation, the protective effects of CPT on the liver were further assessed in HepG2 and LO2 cells, and no appreciable cytotoxic effects were found. Therefore, these findings indicates CPT alleviates liver inflammation via Rho-kinase signaling.